2001
DOI: 10.1159/000047073
|View full text |Cite
|
Sign up to set email alerts
|

Lewis and Secretor Gene Effects on Lewis Antigen and Postnatal Development of Lewis Blood Type

Abstract: Lewis (Le) and Secretor (Se) gene effects on postnatal change in Lewis antigens are described based on the quantitative analysis of Lewis antigens in blood. Genuine Lewis blood types were determined by Le and Se genotyping in DNA samples obtained from umbilical cord blood and infant blood. Lewisa (Lea) and Lewisb (Leb) antigen levels were measured by a time-resolved fluoroimmunoassay. We found that Lewis phenotypes in infants over 9 months of age agreed with the genu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…These genotypic variations in the neonate-specific P[6]VP8* constrain the orientation of the reducing end of the type I glycan restricting its ability to bind branched glycans. This may be an important factor in conferring the age-restricted tropism of certain P[6] strains because precursor glycans and unbranched structures are more abundant in the neonatal gut and branching at the reducing end is developmentally regulated 35 , 42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These genotypic variations in the neonate-specific P[6]VP8* constrain the orientation of the reducing end of the type I glycan restricting its ability to bind branched glycans. This may be an important factor in conferring the age-restricted tropism of certain P[6] strains because precursor glycans and unbranched structures are more abundant in the neonatal gut and branching at the reducing end is developmentally regulated 35 , 42 …”
Section: Resultsmentioning
confidence: 99%
“…Our structural studies provide a possible structural rationale for the neonate specificity observed in some P[6] HRV strains. In the neonate gut, modification to the precursor moieties or the branching at the reducing end is developmentally regulated 35 , 42 . While ABH and Lewis HBGAs are also present, the most abundant type in the neonate gut is the unbranched type I precursor glycans 35 , 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, P[6] strains have been isolated from asymptomatic neonates from South Africa, Venezuela, Australia, Brazil, Sweden and India 38 41 . Furthermore, expression of HBGAs may also be developmentally regulated and different in children <1–2 month of age 42 , and the observed genetic susceptibility may not be absolute, particularly in the very young.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals of Le(a+b+) blood type are Se weak Le+ partial secretors ( 23 ). For Le − individuals, Le(a−b−) can be either Se+ secretors or Se − nonsecretors ( 24 , 25 ). As a result, Le(a+b−) and Le(a−b+) Lewis blood types can be used to directly identify nonsecretor and secretor types of mothers, respectively.…”
Section: Introductionmentioning
confidence: 99%